Internalisasi Nilai-Nilai Agama Dalam Membentuk Moralitas Sosial di Kalangan Anak Usia Dini - Arfriani Maifizar; Faizatul Husna (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
Parents are playing an important role in educating religious values to their children. The morality of future children's behavior is determined by the education and guidance of their parents. In fact, children get their education first in their family. Education in the family runs throughout the ages, through a process of interaction and socialization within the family itself. The value of education is implied in the integrity of the family, both in communication between fellow family members, in the daily behavior of parents and family members. Therefore, parents should always set a good example for their children, because whatever the habits of parents at home will always be imitated by children. The purpose of this study is to focus on the problem of internalization in shaping the morals of children and the values of worship effectively. While in this research, the researcher uses Library Research research that is the collection and analysis of library materials collected from books and various other literature. The results showed that the internalization of religious values that had been embedded from an early age would form good morality. The important role of religious education from parents influences the good behavior of children in the future.